Implementasi Scrum untuk Meningkatkan Adaptivitas Pengembangan Sistem Business Intelligence Pada Perusahaan Distributor Alat Kesehatan - Nursanti Novi Arisa; Indrayanto Dwicaksono; Is Riosena Nur Soffa (Bulletin of Computer Science Research, 2026)
In the Industry 4.0 era, optimizing data utilization has become an important factor in enhancing organizational monitoring effectiveness and decision-making processes. PT Promedika Mitra Utama and PT Promedika Mitra Farma have digitalized various operational aspects, including employee activities, correspondence management, risk management, and weekly reporting. However, the generated data have not been optimally integrated to support managerial analysis. This study aims to design and implement a dashboard-based Business Intelligence (BI) system to improve monitoring effectiveness and managerial information accessibility. The development process includes performance metric identification, data collection and cleansing, data integration, and centralized data storage, with visualization implemented using Google Looker Studio. The Scrum method was applied to accommodate evolving variables and visualization requirements throughout iterative development and stakeholder feedback. The system development was completed in three sprints with a 100% backlog completion rate. Evaluation through sprint reviews and stakeholder validation demonstrated that the dashboard successfully accommodated changing requirements and supported a more systematic and integrated monitoring process. The resulting dashboard consists of three main reports, namely an integrated operational report and weekly reports for each company. The findings indicate the effectiveness of the Scrum approach in developing an adaptive BI system.